Hepatitis C virus: why do we need a vaccine to prevent a curable persistent infection?. (August 2015) - Walker, Christopher M; Grakoui, Arash
Highlights: Hepatitis C virus is a major cause of chronic liver disease. Chronic hepatitis C can be cured, but there is no vaccine to prevent infection. Resolution of infection provides immunity, suggesting that vaccination is possible. Prevention of HCV persistence, and not infection, is the goal of vaccination. Vaccines to elicit neutralizing antibodies or T cells have been assessed in humans. Abstract : Chronic hepatitis C virus infection is now curable by antiviral therapy but the global burden of liver disease is unlikely to diminish without a vaccine to prevent transmission. The objective of HCV vaccination is not to induce sterilizing immunity, but instead to prevent persistent infection. One vaccine that incorporates only non-structural HCV proteins is now in phase I/II efficacy trials to test the novel concept that T cell priming alone is sufficient for protection. Evidence also suggests that antibodies contribute to infection resolution. Vaccines comprised of recombinant envelope glycoproteins targeted by neutralizing antibodies have been assessed in humans for immunogenicity. Here, we discuss current concepts in protective immunity and divergent approaches to vaccination against a highly mutable RNA virus.